2019
DOI: 10.1038/s41598-019-44537-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle dynamics of mouse embryonic stem cells in the ground state and during transition to formative pluripotency

Abstract: Mouse embryonic stem cells (mESCs) can be maintained as homogeneous populations in the ground state of pluripotency. Release from this state in minimal conditions allows to obtain cells that resemble those of the early post-implantation epiblast, providing an important developmental model to study cell identity transitions. However, the cell cycle dynamics of mESCs in the ground state and during its dissolution have not been extensively studied. By performing live imaging experiments of mESCs bearing cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…3C) (p-value = 1.108x10 -8 ). Therefore shortening of the cell-cycle begins prior to exit from naïve pluripotency, as recently proposed(Waisman et al, 2019), and the cell cycle shortens further over subsequent generations(Fig. 3D).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…3C) (p-value = 1.108x10 -8 ). Therefore shortening of the cell-cycle begins prior to exit from naïve pluripotency, as recently proposed(Waisman et al, 2019), and the cell cycle shortens further over subsequent generations(Fig. 3D).…”
supporting
confidence: 68%
“…Generation times reveal that cell division rate also begins to shorten prior to exit from naïve pluripotency. Cell cycle shortening may therefore be an early marker of differentiation , as suggested in a recent report (Waisman et al, 2019) . However, self-renewing ES cells in serum/LIF exhibit a faster cell cycle than 2i cells, with a shortened G1 phase (ter Huurne et al, 2017) .…”
Section: Discussionmentioning
confidence: 70%
“…5E and 5F). This is in agreement with previous reports that indicated that the G2/M state is more associated with pluripotency than the G1 state 54 .…”
Section: During Cellular Differentiation Linage Outcomes Are Not Affsupporting
confidence: 94%
“…Taking a step beyond, we proved that mESCs can memorize morphine exposure and maintain reduced levels of H3K27me3 for a minimum of 4 cell cycles. Considering that mESCs have a cell cycle length of approximately 11–14 h [ 56 ], morphine reduces H3K27me3 levels that persist at least 48 h after treatment removal before recovering to control values. In line with this, transcriptional downregulation of some PRC2 components also persists for 48 h, which implies 4 cell cycles, but not 96 h. While elevated levels of promoter H3K27me3 may well be involved in the initial morphine-induced downregulation of PRC2 genes in the short term, it does not seem necessary for the persistence of this effect through multiple cell divisions.…”
Section: Discussionmentioning
confidence: 99%